2012
DOI: 10.1371/journal.pone.0031906
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Classification of Lung Cancer into Molecular Subtypes

Abstract: The remarkably heterogeneous nature of lung cancer has become more apparent over the last decade. In general, advanced lung cancer is an aggressive malignancy with a poor prognosis. The discovery of multiple molecular mechanisms underlying the development, progression, and prognosis of lung cancer, however, has created new opportunities for targeted therapy and improved outcome. In this paper, we define “molecular subtypes” of lung cancer based on specific actionable genetic aberrations. Each subtype is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 86 publications
(160 reference statements)
0
95
0
1
Order By: Relevance
“…Western blotting confirmed that SKI is often coexpressed with SOX2, OCT4 and KLF4 (Supplementary Figure 7). Considering the fact that, pathologically, lung ADCs carrying Kras and p53 mutations are classified as poorly differentiated, high-grade cancers, 38,39 the expression of pluripotency-associated transcription factors indicates that KrasG12D-generated SCCs are composed of cells that are relatively immature.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting confirmed that SKI is often coexpressed with SOX2, OCT4 and KLF4 (Supplementary Figure 7). Considering the fact that, pathologically, lung ADCs carrying Kras and p53 mutations are classified as poorly differentiated, high-grade cancers, 38,39 the expression of pluripotency-associated transcription factors indicates that KrasG12D-generated SCCs are composed of cells that are relatively immature.…”
Section: Resultsmentioning
confidence: 99%
“…Most cases of lung cancer are diagnosed at advanced stages, with stage IV associated with a 1% 5-year survival rate (1). In the past decade, molecular "driver" mutations have been identified, and small-molecule kinase inhibitors have been developed to target specific molecular aberrations (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inactivating mutations in NOTCH family genes have been identified by whole-genome sequencing in 25% of human SCLC tumors, suggesting that these alterations may represent a major feature of SCLC (25) . NOTCH signaling is critical in the regulation of the neuroendocrine compartment size in the maturaation of lung and its inactivation could therefore contribute to malignant transformation of neuroendocrine cells (2,(27)(28)(29)(30) .…”
Section: Major Molecular Alterations In Lung Cancersmentioning
confidence: 99%